18F-FLUOROESTRADIOL PET/CT IN DIFFERENTIAL DIAGNOSIS OF LUNG LESIONS IN BREAST CANCER PATIENTS: CASE REPORTS - N. В. Vikhrova; A. A. Odzharova; M. В. Dolgushin; D. I. Nevzorov (Сибирский онкологический журнал, 2018)
Background. Breast cancer is the second most common cancer worldwide. Despite significant advances in breast cancer treatment, more than 50 % of patients develop recurrence following completion of treatment. If there is a suspicion of disease progression, the differential diagnosis of metastatic tumor and non-metastatic lesion using the standard imaging methods can be difficult. A modern approach to the detection and assessment of the extension of recurrent disease is individual evaluation of the biological characteristics of the tumor, including determination of the status of estrogen receptors with the goal of adequate treatment. PET/CT with 18F-fluoroestradiol in patients with hormone-dependent breast cancer can be used to determine the expression of estrogen receptors (RE) in tumor tissue and assess the presence of receptor-positive metastases throughout the body in a single study. Case description. We report the cases of 55-year-old and 57-year-old women with hormone-dependent breast cancer after standard treatment (surgery, radiation therapy and hormone therapy). During hormone therapy, lung lesions were detected in both patients. To assess the activity of these lesions, 18F-fluoroestradiol PET/CT was used. In the first case, a low uptake of 18F-FDG was observed. In the other case, no18F-FDG uptake was found. Given that both patients had hormone-dependent breast cancer, it was decided to perform PET/CT with 18F-fluoroestradiol (18F-FES) to evaluate the expression of ER. In the first case, the 18F-FES uptake was detected in all lesions that indicated the evidence of metastases. Histological examination confirmed the evidence of metastatic tumor. In the second case, no uptake of 18FFES was detected in the foci and the patient was followed-up for 6 months. Computed tomography showed decrease in the size of lesions.Conclusion. The use of 18F-FES PET/CT can be an important diagnostic tool for detection of disease progression in patients with hormone-dependent breast cancer. In case of detection of positive foci on 18F-FES PET/CT scans, hormone therapy for breast cancer can be administered without invasive procedures for verifying the diagnosis.